Subcutaneous emphysema during restorative dentistry - ROBERT J. STEELMAN, & PHYLLIS W. JOHANNES (IAPD and Blackwell, 2007)
Subcutaneous emphysema is a rare occurrence in the dental setting. When it does occur,the entity may be mistaken for an anaphylactic reaction to a local anaesthetic agent or other medications used in dental surgery.